MATARANINE A AND B: A NEW DIASTOMERIC INDOLE ALKALOID FROM Alstonia scholaris R.Br. OF LOMBOK ISLAND - Surya Hadi (Indonesian Journal of Chemistry, 2009)
Alstonia scholaris R. Br., (Apocynaceae) is widely distributed in Indonesia and in Lombok Island, the plant locally known as ";lolon nita"; has been used to treat malaria. To locate potential bioactive compounds, acid-base extraction was carried out. From the base fraction, two new indole alkaloids with diastomeric structure, named Mataranine A and B, were isolated. The structures of the two alkaloids were elucidated on the basis of UV, NMR and mass spectral data.